Climate risk assessment and agricultural value chain prioritisation for Malawi and Zambia - Vergage, Fabian; Cramer, Laura K.; Thornton, Philip K.; Campbell, Bruce M. (2018)
Climate change is projected to have serious impacts on the agriculture of southern Africa, affecting food availability, creating local production shortfalls and resulting in rising commodity prices. This report highlights the risks to agriculture and food systems that may occur in two counties of the region, Malawi and Zambia. The analysis uses the conceptual framework of climate-related risk from the Fifth Assessment Report of the Intergovernmental Panel on Climate Change to examine the impacts that climate change is likely to have on agriculture and food security. Country-specific trends in temperature and rainfall and projected impacts are summarised from the literature. The vulnerability of the agricultural sector in each country is discussed in relation to its sensitivity to change and coping and adaptive capacity, and the risks of climate change on agriculture and small-scale farmers in the two focus countries assessed. A prioritisation process is then carried out to rank different commodities in each country, with respect to four dimensions: the importance of the commodity to the economy of the country, the national yield gap compared with the regional average, the importance of the commodity in people’s diet, and the projected impact of climate change on yield. The results of the analysis highlight three commodities that could be prioritized for agricultural development interventions: maize, potatoes and beans in Malawi, and maize, pulses and sorghum in Zambia.